HRM AS A MARKETING FUNCTION: SELLING EMPLOYER BRANDING, ORGANIZATIONAL CULTURE, AND CORPORATE IMAGE TO PROSPECTIVE EMPLOYEES IN A MEDIATED MODEL - Mohamed Alkashami; Ebtisam Labib; Habil Slade (Fonseca, Journal of Communication, 2025)
This study explores the role of HRM as a marketing function in shaping organizational attractiveness and its subsequent effects on employee recruitment outcomes. Using a quantitative approach, we tested the relationships between Employer Branding, Organizational Culture, Corporate Image, Organizational Attractiveness, and Employee Recruitment Outcomes. The findings reveal that while organizational attractiveness serves as a key mediator between organizational culture and recruitment outcomes, the relationships between employer branding, corporate image, and organizational attractiveness were not as expected. Contrary to existing literature, employer branding and organizational culture were found to have a negative influence on organizational attractiveness, potentially due to misalignments between branding messages and actual workplace experiences. The study’s findings underscore the complexity of integrating marketing principles into HRM and highlight the need for authenticity in employer branding to effectively attract and retain top talent.